RELIABILITY AND VALIDITY OF THE LATVIAN VERSION OF THE COMPUTERIZED EXECUTIVE FUNCTIONS TEST “EXAMINER” IN A STUDENTS SAMPLE: RESULTS OF THE PILOT STUDY - Ivanova, Liena; Plauca, Ilze; Sebre, Sandra; Rascevska, Malgozata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The aim of this pilot-study was to assess reliability and validity of the Latvian version of the computerized executive functions test EXAMINER (Executive Abilities: Measures and Instruments for Neurobehavioral Evaluation and Research) in a sample of high school students and university students. The adaptation procedure included translation of the instructions and technical configuration of the test’s computerized version. The Latvian version of the EXAMINER includes tasks that measure executive functions of inhibition, set shifting and working memory updating. Participants included two sub-groups: 22 (14 males, 8 female) students from high school and 39 students (11 males, 28 female) from university.  Results showed statistically significant differences between both sub-groups on most of the EXAMINER tasks. The main tendency was that the high school students showed faster reaction time, but made more mistakes. Results also showed good reliability for most of the EXAMINER tasks and good criterion validity. Potential improvements of the test and its potential use in schools and clinics are discussed.